Pola Asuh yang Diterapkan dalam Keluargaku dan Dampaknya pada Kemandirian Anak - Suriani Suriani; Eka Eka; Sapira Sapira; Juwita Juwita; Asmita Asmita; Rosita Rosita; Siti Nur Hasanah; Ririn Anggraeni; Kalbi Jafar (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The family plays a crucial role as the primary environment shaping a child's character development and independence, making parenting a key factor in this process. This study aims to describe the parenting styles applied in the researcher's family and analyze how these styles influence the development of children's independence. The study employed an autoethnographic method with a descriptive qualitative approach, in which the researcher reflected on five years of parenting experiences through participant observation, daily journals, and informal interviews. The results indicate that the parenting style applied is democratic, characterized by open communication, flexible rule implementation, gradual assignment of responsibilities, and consistent emotional support. This parenting style has a positive impact on the development of children's independence, as evidenced by the children's ability to complete tasks independently, make decisions, regulate emotions, and demonstrate initiative in daily activities. This study concludes that democratic parenting can be an effective approach to building children's independence, although adjustments need to be made based on the character and needs of each child.